1999
DOI: 10.1159/000045489
|View full text |Cite
|
Sign up to set email alerts
|

Serum Paraoxonase Activity Changes in Uremic and Kidney-Transplanted Patients

Abstract: Serum paraoxonase (PON) is a high-density lipoprotein (HDL)-associated hydrolase, which inhibits low-density lipoprotein oxidation. Uremic and kidney-transplanted patients have an increased risk of atherosclerosis, to which an increased lipoprotein oxidation may contribute. The aim of our study was to determine whether the PON activity or phenotype is altered in uremic and kidney-transplanted patients, and to compare the values with those of healthy controls. 117 uremic patients on long-term hemodialysis treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 28 publications
5
36
0
2
Order By: Relevance
“…Previous studies have indicated that PON1 can prevent low density lipoprotein (LDL) oxidation by hydrolyzing lipid peroxides in lipoproteins, deoxify homocysteine thiolactone and therefore protect against the development of atherosclerosis [2][3][4]. The enzyme's activity is reduced in patients with enhanced atherosclerosis, in disorders of lipoprotein metabolism, in renal insufficiency and after renal transplantation, caused by elevated oxidative stress and disturbances of apolipoprotein metabolism [5]. PON1 has newly been discovered to possess lactonase activity, and hydrolyze various lactones, thiolactones and cyclic carbonate esters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that PON1 can prevent low density lipoprotein (LDL) oxidation by hydrolyzing lipid peroxides in lipoproteins, deoxify homocysteine thiolactone and therefore protect against the development of atherosclerosis [2][3][4]. The enzyme's activity is reduced in patients with enhanced atherosclerosis, in disorders of lipoprotein metabolism, in renal insufficiency and after renal transplantation, caused by elevated oxidative stress and disturbances of apolipoprotein metabolism [5]. PON1 has newly been discovered to possess lactonase activity, and hydrolyze various lactones, thiolactones and cyclic carbonate esters.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we [4] and others [5] demonstrated decreased PON1 activity in HD patients, and kidney transplantation can partially reverse it [6]. Cardiovascular diseases and accelerated atherosclerosis are known complications in HD patients, and the enhanced oxidative stress [7, 8] is concomitant with the decreased antioxidant defense system [4, 5] measured also by α-tocopherol levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…14 Another study concluded that immunosuppressive drug combinations do not affect PON activity. 15 After a kidney transplant, continuous immunosuppressive therapy (cyclosporine, azathioprine, and methylprednisolone) produced other predisposing factors for accelerating atherosclerosis. 15 Arterial stiffness may be a marker for the development of future atherosclerotic disease or may be more directly involved in the process of atherosclerosis in uremic and nonuremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,[10][11][12] Low PON1 levels in uremic patients have been restored after kidney transplant. 5,[13][14][15] However, there are few studies that compare the effect of calcineurin inhibitors on oxidant and an antioxidant system indices in kidney transplant recipients. [16][17][18][19][20] The purpose of this prospective study was to evaluate the effects of the calcineurin inhibitors tacrolimus and cyclosporine on cardiovascular disease risk factors, including high-sensitivity CRP (hsCRP), homocysteine, malondialdehyde (MDA, a lipid peroxidation biomarker of oxidative stress), and activity of PON and arylesterase (components of the antioxidant system), in kidney transplant recipients.…”
mentioning
confidence: 99%